2018
DOI: 10.1523/eneuro.0466-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 Interacts with VCP/p97 and Activates PKA to Promote NSFL1C/p47 Phosphorylation and Dendritic Arborization in Neurons

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 95 publications
2
34
0
Order By: Relevance
“…Neuritic shortening is a common pathological change in neurodegenerative diseases and has been reported in multiple PD models to include 6-OHDA, PINK1 knockdown, and mutant LRRK2 (15,30,(71)(72)(73). Here, we found that overexpression of PINK1 reversed the MPP+-induced neurite shortening, consistent with the previously reported role of PINK1 in promoting dendrite outgrowth (15,52). These pro-differentiation effects of PINK1 may be mediated through indirect activation of Akt (53) or by the ability of PINK1 to phosphorylate and activate PKA (52).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Neuritic shortening is a common pathological change in neurodegenerative diseases and has been reported in multiple PD models to include 6-OHDA, PINK1 knockdown, and mutant LRRK2 (15,30,(71)(72)(73). Here, we found that overexpression of PINK1 reversed the MPP+-induced neurite shortening, consistent with the previously reported role of PINK1 in promoting dendrite outgrowth (15,52). These pro-differentiation effects of PINK1 may be mediated through indirect activation of Akt (53) or by the ability of PINK1 to phosphorylate and activate PKA (52).…”
Section: Discussionsupporting
confidence: 91%
“…Here, we found that overexpression of PINK1 reversed the MPP+-induced neurite shortening, consistent with the previously reported role of PINK1 in promoting dendrite outgrowth (15,52). These pro-differentiation effects of PINK1 may be mediated through indirect activation of Akt (53) or by the ability of PINK1 to phosphorylate and activate PKA (52). In addition, PINK1 may influence neurite outgrowth through its effects on mitochondrial trafficking (15), as the ability to deliver mitochondria plays a limiting role in synaptogenesis (74,75).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Parkin also indirectly interacts with cytosolic proteins, F-actin functional ARP4/5, and directly with VCP/p97 associated with mitophagy activation. PINK1 is well-known to interact with Parkin and VCP/p97, after which this complex regulates dendritic arborization [65]. Based on these results, we hypothesize that Parkin regulates organelle cross-talk potentially transferring external signals to internal platelet environments and cell-cell cross-talk among other cells.…”
Section: Discussionmentioning
confidence: 71%
“…Many genes with DIE have DP£ 0.5; however we also identified drastic switches (DP³0.5): Nsfl1c encodes the Nsfl1 cofactor p47, which regulates tubular ER formation, influences neuronal dendritic spine formation and dendritic arborization 37,38 . A 6nt microexon is preferentially included in HIPP across neuronal and glial cell types but is absent in the same PFC cell types (Fig 2h).…”
Section: A Gene-wise Test To Determine Differential Isoform Expressiomentioning
confidence: 87%